Jasmine Toguchi, peace-maker - Florence, Debbi Michiko (Florence, Debbi Michiko. Jasmine Toguchi, 2023)
Eight-year-old Jasmine travels to Hiroshima to visit her grandmother and cousin. Includes author's note and instructions on how to make an origami dove.